A - Peter (Oxford University Press, 2004)
The Dictionary of Christian Art, now rebranded in the best-selling Oxford Paperback Reference series, is a unique and fascinating exploration of the art and architecture that has been influenced and inspired by biblical stories and Christian history and beliefs. The Dictionary combines general essays on the periods and styles important in the history of Christian art with lots of shorter entries that describe specific works, artists, themes, and visual images, and which give the reader practical guidance on where in Europe to locate the works described.